2016
DOI: 10.1007/s11255-016-1465-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between serum paraoxonase activity and epicardial adipose tissue in hemodialysis patients

Abstract: Our study demonstrated that PON-1 activity was significantly lower in HD patients compared with healthy controls and that PON-1 activity was inversely correlated with EATT in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In a cross-sectional study of 72 hemodialysis patients, a low HDL cholesterol level was identified as an independent risk factor of elevated EAT thickness. 19 A meta-analysis showed that there was a highly significant (p < 0.001) correlation between EAT thickness and HDL cholesterol. 5 Our results confirm the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of 72 hemodialysis patients, a low HDL cholesterol level was identified as an independent risk factor of elevated EAT thickness. 19 A meta-analysis showed that there was a highly significant (p < 0.001) correlation between EAT thickness and HDL cholesterol. 5 Our results confirm the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is another mechanism responsible for increased risk other than infiltration. Previous studies have shown a positive correlation between EFT and serum oxidant content and a negative correlation with anti oxidant content (16)(17).…”
Section: Discussionmentioning
confidence: 84%
“…However, a few females in the grade 3 with very low PON1 levels and males in the grade 1 with high PON1 levels suggested that differences in serum PON1 levels might be, not only gender-dependent, but also dependent of a certain genetic factor(s). Certain polymorphic variants of human PON1 showed high enzyme activities and a positive association with the fatty acid composition in the body [8,9]. The positive association of serum PON1 levels with meat quality implicates the PON1 polymorphism that needs to be investigated for the genetic improvement of Hanwoo.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphic variants of human PON1 were reported to be significantly different in the enzyme activity of PON1 showing a positive association with the fatty acid composition of the adipose tissue [8]. Another study demonstrated an inverse correlation of PON1 activity with the thickness of epicardial adipose tissue, which suggested a possible role of PON1 in the regulation of the lipid composition in body [9].…”
Section: Introductionmentioning
confidence: 99%